Determinants of capital adequacy and voluntary capital buffer among microfinance institutions in an emerging market - King Carl Tornam Duho (Cogent Economics & Finance, 2023)
This study examines the determinants of capital adequacy and voluntary capital buffers among microfinance institutions (MFIs). We apply the two-stage least squares (2SLS) with instrumental variables to account for endogeneity. Using quarterly panel data of 439 MFIs in Ghana covering the period 2015-2018, the study found that credit risk, income diversification, size, profitability, lending channel, and equity-to-asset ratio significantly affect capital adequacy. Also, the factors that drive voluntary capital buffers are income diversification, size and equity-to-asset ratio, but size and economic growth are insignificant when the upper limits of Basel III requirements are applied. Generally, the results are insignificant among non-deposit-taking (i.e. Tier 3 like Financial NGOs) MFIs. The findings show that non-performing loans negatively affect capital adequacy. Income diversification increases capital adequacy, especially among deposit-taking MFIs which have the regulatory liberty to engage in additional financial intermediation activities. Size has an inverted U-shape nexus with capital adequacy and there is evidence to suggest that for non-deposit-taking MFIs, size may not matter. Profitability increases capital adequacy while equity-to-asset ratio decreases capital adequacy, especially among deposit-taking MFIs. Additionally, lending channels negatively affect capital adequacy, especially among deposit-taking MFIs. Economic growth reduces capital adequacy but results are insignificant when we control for quarter fixed-effects. These results throw light on the application of the capital buffer theory in the context of MFIs which provides useful insights for practitioners, regulators, policymakers and academia.
Keywords: G21; G23; G32; L25; N27; P46; 330; Basel accord; capital adequacy; emerging markets; financial risk regulation; microfinance institutions; non-performing loans; pro-poor population